Analisis Intensitas Konsumsi Energi RS Medirossa Cikarang - Sielvya Rahma Maulida; Mia Galina; Joni Welman Simatupang (President University, 2019)
Medirossa Hospital is one of the health care centers in the city of Cikarang which in its operations does not only focus on the customer excellent services but also pay attention to the comfort of the environment and the completeness of the health facilities. One factor that determines the convenience of a hospital is the intensity of lighting. From the observations made by the authors of several rooms at Medirossa Cikarang Hospital, namely the casemix room, medical records, VIP treatment, and the hall leading to the second floor has less bright lighting. This observation was carried out by surveying 26 respondents who were hospital employees and visitors. From the observation, 53% of respondents stated that the room was